Folksonomized Ontologies – from social to formal - Alves, Hugo; Santanchè, André (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
An ever-increasing number of web-based repositories aimed at sharing content, links or metadata rely on tags informed by users to describe, classify and organize their data. The term folksonomy has been used to define this “social taxonomy”, which emerges from tagging carried by users interacting in social environments. It contrasts with the formalism and systematic creation process applied to ontologies. In our research we propose that ontologies and folksonomies have complementary roles. The knowledge systematically organized and formalized in ontologies can be enriched and contextualized by the implicit knowledge which emerges from folksonomies. This paper presents our approach to build a “folksonomized” ontology as a confluence of a formal ontology enriched with social knowledge extracted from folksonomies. The formal embodiment of folksonomies has been explored to empower content search and classification. On the other hand, ontologies are supplied with contextual data, which can improve relationship weighting and inference operations. The paper shows a tool we have implemented to produce and use folksonomized ontologies. It was used to attest that searching operations can be improved by this combination of ontologies with folksonomies.